Peningkatan Reputasi Perusahaan Di Indonesia Melalui Sumber Pembiayaan Berbasis Green bond Dan Green sukuk - Endri Juniyanto; Atika Ulfah (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2026)
The objective of this research is to empirically examine how financing through green bonds and green sukuk impacts the improvement of corporate reputation within Indonesia.  Employing a quantitative methodology, this research utilizes secondary data extracted from the statistical reports of OJK and BEI over the 2019–2023 period. The sample selection technique was carried out using a purposive sampling method, resulting in a sample of 31 green bond series and 45 green sukuk series from various public companies. The data were analyzed using linear regression tests facilitated by the SEM-AMOS software.  The findings indicate that both financing instruments yield a positive impact.  Specifically, green bonds demonstrate a significant influence on corporate reputation (p < 0.027). Similarly, green sukuk also exhibit a substantial effect on corporate reputation, supported by a significance value of (<0.015).